Establishment survey participation during the COVID-19 pandemic - Benjamin Küfner; Joseph W. Sakshaug; Stefan Zins (Journal for Labour Market Research, 2022)
Establishment surveys around the globe have measured the impact of the COVID-19 pandemic on establishments' conditions and business practices. At the same time, the consequences of the pandemic, such as closures, hygiene standards, or remote work arrangements, may have also altered patterns of survey participation and introduced nonresponse bias, threatening the quality of establishment survey data. To investigate these issues, this article examines fieldwork outcomes, nonresponse bias, and predictors of survey participation in the IAB-Job Vacancy Survey. As comparisons with previous survey years show, it became more difficult to successfully interview establishments during the COVID-19 pandemic. Using linked administrative data, we show that nonresponse bias was higher in 2020 compared to previous years, even after applying the standard weighting adjustment. However, general patterns of survey participation in 2020 were similar to previous years and COVID-19 related measures were not strong predictors of survey participation in 2020. Further, we provide evidence that nonresponse bias during the pandemic can be reduced by incorporating additional administrative variables into the weighting procedure relative to the standard weighting variables. We conclude this article with a discussion of the findings and implications for survey practitioners.
Keywords: C83; 330; Fieldwork efort; Nonresponse bias; Data collection; Weighting adjustment administrative data; IAB Job Vacancy Survey